SUITABLE DISPLACEMENT METHOD FOR HEAVY OIL AND LOW TEMPERATURE CASE ON SANDSTONE RESERVOIR (ANALYSIS LABORATORY) - PRATAMA KESUMA (NIM : 22216014), WIDYA
The decline of Indonesian petroleum production is due to the decrease in the amount of Indonesian petroleum reserves found. One effort to tackle the decline of oil production by EOR technology is chemical flooding using surfactant which aims to reduce the inter-face tension between oil and water and carry oil that can not be carried by water, in addition to increase the maximum oil gain possible (100%), the surfactant may also reduce the amount of oil trapped in the reservoir (Saturation Oil Residue or Sor). This research was conducted in Enhanced Oil Recovery laboratory, Petroleum Engineering Study Program ITB. The main experiments in this study were imbibition test, wettability on artificial sandstone with surfactant G03 and G04. The imbibition test was performed using a surfactant with concentrations of 2%, 2.5% and 3% concentrations respectively at 400C. The results of the study, the best surfactant is that can produce the lowest viscosity value at the fraction of oil volume below 50%. The result of mixed viscosity measurement, G04-3% surfactant at 40oC gives the lowest mixed viscosity value. In the IFT test, the surfactant G04 has a lower IFT value than the surfactant G03. Therefore, based on IFT test, the best chemical surfactant is G04-3% because it is able to convert oil wet to water wet and has the lowest contact angle. In the wettability test, surfactant concentration is able to make changes in wettability of rocks from oil wet to water wet so that the oil trapped inside the pore more easily flow with water and improve oil recovery factor. In the coreflooding test, core flooding test I & II total recovery factor has not reached 100%. After coreflooding III was tested at 40 oC with superadditive added, the recovery factor was 100%. To see the performance of chemical used, coreflooding IV was tested with temperature decreased to 37 oC without using waterflooding obtained 100% fixed factor recovery result. This means superadditive greatly affect recovery.